MORFOMETRI DAERAH ALIRAN SUNGAI PADA BENTANGALAM VULKANIK KWARTER TERDEFORMASI - -, Emi Sukiyah; -, Mulyono (Fakultas Teknik Geologi Universitas Padjadjaran, 2007)
The Quaternary volcanic terrain has unique characteristic. Those phenomena are reflected by basin morphometry. Some morphometry variables can used are basin dimention, azimuth of river segment, azimuth of terrain lineament, river length (Ls), drainage density (Dd), and bifurcation ratio (Rb).Upper Citarum River area is the research area, exactly on Cijoho Basin, Cihejo Basin, Cigalugah Basin, and Barugbug Basin. Base on literature study result and field survey, those four basins have difference geological setting. Probabilistic approach used for know difference and similarity of basins. Statistic tests used are distribution normality of data and average difference tests.Result of research show highest Dd value exist on Cijoho Basin (3.78), otherwise its lowest exist on Barugbug Basin (2.35). That’s phenomena reflect difference of its volcanic rock characteristic. Commonly Rb values < 3 show that deformed basins. Rb values increase to downstream of Cihejo Basin, meanwhile on the other basins they are decrease. The Rb values escalation to downstream indicate strongly deformation at downstream of Cihejo Basin. The rivers of Cijoho Basin direct the-90o until 179o controlled by active tectonic. Meanwhile, the rivers pattern of Basins of Cihejo, Barugbug, and Cigalugah are controlled by active tectonic.